2020
DOI: 10.14198/jhse.2021.164.18
|View full text |Cite
|
Sign up to set email alerts
|

Grit-passion and grit-perseverance in ultramarathon runners

Abstract: The purpose of this study was to investigate the relationship between ultramarathon running, grit-passion, and grit-perseverance. A total of 153 ultramarathon runners (age = 40.5  9.0 years) answered demographic questions and completed a survey measuring subcomponents of grit via Google Forms. Grit was measured with the 12-item Grit Scale consisting of two subscales: consistency of interest (grit-passion) and perseverance of effort (grit-perseverance). The ultramarathon runners were recruited through emails f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Although the relations of grit's components, CI and PE, and practice on the one side, and performance on the other, are less clear (Ansah & Apaak, 2019;Cousins et al, 2020;Tedesqui & Young, 2017, 2018, we can assume that one component will be stronger than the other in a model where both are entered simultaneously as predictors of DP and skill. CI and PE are correlated at least moderately with each other in studies (average r =.43; Guo et al, 2019), which means that one component, the stronger one, will take over a good share of the explained variance common for both components.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the relations of grit's components, CI and PE, and practice on the one side, and performance on the other, are less clear (Ansah & Apaak, 2019;Cousins et al, 2020;Tedesqui & Young, 2017, 2018, we can assume that one component will be stronger than the other in a model where both are entered simultaneously as predictors of DP and skill. CI and PE are correlated at least moderately with each other in studies (average r =.43; Guo et al, 2019), which means that one component, the stronger one, will take over a good share of the explained variance common for both components.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have reported that PE (and not CI) differentiate between skilled athletes of different disciplines, including soccer (Tedesqui & Young, 2017, 2018. Others, however, have reported that both PE and CI are predictive of future success in athletes taking part in the university sports competitions (Ansah & Apaak, 2019) or that only CI is associated with longer tenure for ultramarathon runners (Cousins et al, 2020).…”
Section: Grit and Its Relation To Dpmentioning
confidence: 99%
See 1 more Smart Citation